Xinjiang: Prospect for development and challenges for the new administration - Rogers, R.A. (2013)
Xinjiang or ‘the new territory’ is unique because it is the only of the Chinese province located in Central Asia. Xinjiang can be considered a ‘bridge’ linking China with the Central Asian republics as well as other countries in the Caucasus region. Xinjiang has been a strategic area since the ancient times due to it being part of the ‘Silk Road’, which was a popular route used by traders and travellers between the East and the West. Since 1978 when Deng Xiaoping took over the leadership of China after the demise of Mao Zedong in 1976, China including Xinjiang witnessed dramatic changes in the economic and political situation. These included development projects in the urban and rural areas, modernization of facilities, increase of foreign investments and job opportunities, freedom in performing religious obligations such as pilgrimage, for the Muslim Uyghurs, freedom to practice their culture and language. Hence, there was an overall improvement in livelihood in Xinjiang province. However, political violence and separatist activities in the province have increased since the 1980s and 1990s despite some conciliatory measures which were undertaken by the Chinese administration. This article examines the economic prospect of the province and the political challenges it encounters. In addition, it also analyses the possible strategies that the new Chinese leaders can take into consideration to overcome the security problems in the province.